Mengembangkan Psikologi Konservasi Melalui Model Perilaku Ekologis Mangrove - Akhmad Fauzie (Jurnal Psikologi Teori dan Terapan, 2017)
This study was aimed to examine the mangrove ecological behavior model and the influences of self-concept, environmental ethics, environmental attitude and behavior intention on mangrove ecological behavior. The mangrove ecological behavior model can be useful to promote conservation psychology. The mangrove ecological behavior is constructed based on  the theory of planned behavior that is combined with norm activation theory. Sample used in this study was 235 students in Hang Tuah University. Data were analyzed using path analysis to determine the direct and indirect effect of exogenous variables on endogenous variable. There are two structural equations that is direct and indirect effect of self-concept, environmental ethics, environmental attitude toward mangrove ecological behavior with behavior intention as a mediator variable. The results show that  all structural equations fulfill egilibility. The effect of self-concept, environmental ethics and environmental attitudes on behavior intention amounted to 47.2%, while environmental attitudes give the most effect on behavior intention of 55%. The combined effect of self-concept, environmental ethics, environmental attitudes and behavioral intentions toward mangrove ecological behavior is 27.2% and ecological behavior intention contributed 46.2% toward mangrove ecological behavior. The direct effect of the environmental ethics toward mangrove ecological behavior is 0126, while the indirect effect of environmental ethics towards mangrove ecological behavior through behavioral intention is 0.0549. It can be seen from the result that the effect of the environmental ethics on mangrove ecological behavior is minor. Thus, based on these results, to encourage mangrove ecological behavior, the environmental ethics teaching model needs to be applied. The  focus of this teaching model should be given on environmental attitudes that includes the incease of knowledge and value to the mangrove environment.Abstrak: Penelitian ini menguji model perilaku ekologis mangrove dengan mengukur pengaruh konsep diri, etika lingkungan, sikap lingkungan dan intensi perilaku terhadap perilaku ekologis mangrove. Model perilaku mangrove ini dapat berguna untuk mengembangkan psikologi konservasi. Rancangan model ini didasarkan pada teori perilaku terencana yang dikombinasikan dengan teori aktivasi norma. Sampel penelitian ini berjumlah 235 orang. Analisis data menggunakan analisis jalur (path analysis) karena bertujuan untuk mengetahui pengaruh langsung dan tidak langsung variabel-variabel exogenous terhadap variabel endogenous. Berdasar analisis data diperoleh hasil bahwa semua model persamaan struktur memenuhi kelayakan. Pengaruh konsep diri, etika lingkungan dan sikap lingkungan secara gabungan terhadap intensi perilaku sebesar 47.2% sedangkan pada besaran pengaruh parsial, sikap lingkungan memberi pengaruh paling besar terhadap intensi perilaku sebesar 55%. Pengaruh konsep diri, etika lingkungan, sikap lingkungan dan niatan perilaku terhadap perilaku ekologis secara gabungan sebesar 27.2% dan intensi perilaku ekologis memberi sumbangan terbesar yaitu 46.2%. Pengaruh langsung etika lingkungan terhadap perilaku ekologis adalah -0.126, sedangkan pengaruh tidak langsung etika lingkungan terhadap perilaku ekologis melalui niatan perilaku adalah 0.0549. Hal ini menunjukkan bahwa pengaruh etika lingkungan terhadap perilaku ekologis adalah kecil. Maka, berdasar hasil tersebut, untuk mendorong perilaku ekologis mangrove perlu diterapkan model pembelajaran etika lingkungan hidup difokuskan pada sikap lingkungan yang meliputi peningkatan pengetahuan dan nilai terhadap lingkungan.